Mental Disorder Recognition Using Face Based Image Retrieval Technique In The Compressed Domain (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
In this paper we explore content based image retrieval to identify mental disorder based on face expression the compressed domain. The work was conducted by constructing an application or tool which automatically detect and recognize someone experienced mental disorder based on face recognition. In this research we used more than 50,000 face images which consist of normal face expression with smile, sad, laugh,and angry expression. We wrote two face detection and face recognition algorithms to decide whether someone suffered or not. This work was carried out to built an automatic tool of face detection and recognition very fast and accurately. Face detection done to separate between face area and non face area in order focus on face recognition. In this work we used face image with normal pose without obstacles and facing toward with 90 degree. In the experiments we applied more than 150 queries which 50 images from each category of total of two categories mental disorder. Our algorithms demonstrate good effectives of image retrieval in term of Precision and recall.